Prevention of cardiovascular disease and eating behavior in group of women and men aged 20 to 30 years - Dobrzyńska, Małgorzata; Przysławski, Juliusz (Journal of Medical Science, 2014)
Introduction. Proper nutrition and the use of preemptive care can prevent the development of cardiovascular diseases, which are the main cause of death in the world. Aim. The aims of this study were to evaluate the nutritional habits, nutritional status, assessment of knowledge and use of nutritional prevention among group of women and men aged 20 to 30 years, living in Wielkopolska in the aspect of CVD risk.Material and methods. In this study the method of 24-hour dietary recall to evaluate nutrition intake was used. To determine the nutritional status the anthropometric measurements (weight, height, waist) were taken, and BMI values were calculated. Assessment of knowledge and use of nutritional prevention in cardiovascular disease was performed by a questionnaire. The atherogenicity of the diets was evaluated using Keys score.Results. The analysis of daily food rations showed differences between dietary guidelines and respondent diets, mainly in protein, fat, saturated fat and cholesterol intake. Tested prevention factors were well known in both groups. The exception involved the reduction of sodium intake in the diet. The use of preventive factors in daily routine differentiated treatment in groups. In the studied group men often exercised regularly, while women often limited intake of animal fats, cholesterol and simple sugars.Conclusion. Inadequate nutrition (mainly incorrect saturated fatty acids (SFA), cholesterol and dietary fiber intake) and insufficient prevention care in the studied group may increase the risk of cardiovascular disease in the future.